Japan and the Origins of the Asia-Pacific Order - Hattori, Ryuji. author. aut Link
XV, 167 p. 1 illus.
Keywords: This book analyzes Ohira's ideology, philosophy, and actions as a politician and a minister, based on primary sources from Japan and the USA, and makes a significant contribution to the field of Japanese political and diplomatic history. This book is the first critical biography to chart Masayoshi Ohira’s life and work, with a focus on his political philosophy, and how he sought to create a new order in the Asia-Pacific region, framing a plan for solidarity across the Pacific Rim. If a statesman is a politician who has made diplomacy their life's work, then Ohira can be regarded as the first Japanese statesman of the modern era. While this ambition remained unfulfilled, Ohira's involvement in foreign policy was long and intensive—and highly influential—on the region. One of only two postwar prime ministers to have served as foreign minister for two terms, he attempted to balance the pursuit of a new order in the Pacific Rim with Asian diplomacy and focused on cooperation with the USA without becoming overly reliant on it. With the new availability of original documents decades after his death, this book has become possible, enabling the author to systematically follow and record Ohira's diplomatic vision. Combining history, political philosophy, political science, and international relations, this book is of appeal to history scholars and students of Japan, as well as of the foreign relations of countries such as the USA, China, and Korea.